Sharpea azabuensis: a ruminal bacterium that produces trans-11 intermediates from linoleic and linolenic acid. Issue 7 (17th May 2019) - Dewanckele, Lore; Vlaeminck, Bruno; Fievez, Veerle
Abstract : To investigate the metabolism of 18:2 n -6 and 18:3 n -3 by pure cultures of Sharpea azabuensis, two different strains (RL 1 and ST18) were each incubated in the presence of 40 µg ml -1 18:2 n -6 or 18:3 n -3. Pure cultures of Butyrivibrio fibrisolvens D1 and Butyrivibrio proteoclasticus P18 were included as control treatments. Similar to the metabolism of B. fibrisolvens, both S. azabuensis strains converted 18:2 n -6 or 18:3 n -3 to cis -9, trans -11 CLA or cis -9, trans -11, cis -15 CLnA, after which it was further reduced to trans -11 18:1 or trans -11, cis -15 18:2, respectively. B. proteoclasticus additionally reduced trans -11 18:1 to 18:0. Trans -11, cis -15 18:2 was also further metabolized by B. proteoclasticus, although trans -11 18:1 did not accumulate, and only minor amounts of 18:0 were formed. The time frame of 18:2 n -6 and 18:3 n -3 biohydrogenation by S. azabuensis was comparable with B. fibrisolvens, indicating that S. azabuensis and B. fibrisolvens might be alternative biohydrogenators of 18:2 n -6 and 18:3 n -3 in the rumen.